Correction: taxonomical over splitting in the Rhodnius prolixus (insecta: hemiptera: reduviidae) clade: are R. taquarussuensis (da Rosa et al., 2017) and R. neglectus (Lent, 1954) the same species? (2019)
The use of subtle features as species diagnostic traits in taxa with high morphological similarity sometimes fails in discriminating intraspecific variation from interspecific differences, leading to an incorrect species delimitation. A clear assessment of species boundaries is particularly relevant in disease vector organisms in order to understand epidemiological and evolutionary processes that affect transmission capacity. Here, we assess the validity of the recently described Rhodnius taquarussuensis (da Rosa et al., 2017) using interspecific crosses and molecular markers. We did not detect differences in hatching rates in interspecific crosses between R. taquarussuensis and R. neglectus (Lent, 1954). Furthermore, genetic divergence and species delimitation analyses show that R. taquarussuensis is not an independent lineage in the R. prolixus group. These results suggest that R. taquarussuensis is a phenotypic form of R. neglectus instead of a distinct species. We would like to stress that different sources of evidence are needed to correctly delimit species. We consider this is an important step in understanding vectorial Chagas disease spread and transmission.